Pengaruh rational emotive behaviour therapy (REBT) terhadap kemampuan remaja dalam mengelola emosi - Naibaho, Amelia Elisabeth; Daulay, Wardiyah; Purba, Jenny Marlindawani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Introduction: Adolescence is a transitional period from childhood to adulthood. During adolescence, hormonal, physical, and psychological changes occur gradually. The ability to control emotions differs from suppressing them. Rational emotive behavior therapy (REBT) focuses on how people think, feel, and act to cope with emotions. Purpose: To identify the effect of rational emotive behavior therapy (REBT) on adolescents' ability to manage emotions. Method: A quantitative, quasi-experimental, pre-post control group approach was used. The sampling technique used purposive sampling, with a total sample of 80 participants divided into 40 intervention groups and 40 control groups. Data were analyzed using univariate and bivariate analyses (dependent t-test). Results: Before the intervention, the majority of adolescents in the intervention group were in the moderate (34 (85%), high (4 (10%), and low (2 (5%).) After the intervention, there was a significant improvement, with 31 (77.5%) adolescents in the high category of emotional management skills and 9 (22.5%) in the moderate category. In the control group, which only received counseling from guidance counselors, there was no significant improvement. The number of adolescents with high emotional management skills decreased from 7.5% to 0%, while the majority remained in the moderate category. Statistical tests showed a highly significant difference between the intervention and control groups (p = 0.001), with the average emotional management skill score being significantly higher in the group receiving REBT. Conclusion: There was a difference in emotional management in the intervention group before and after REBT (p-value = 0.001). There was no difference in emotional management in the control group before and after receiving counseling from guidance counselors (p-value = 0.766). REBT can have a significant impact on emotional management in adolescents. Suggestion: Implement REBT in groups can be an effective intervention strategy in helping adolescents manage their emotions in healthier, more rational, and adaptive ways. Keywords: Adolescents; Emotions; Rational Emotional Behavior Therapy (REBT). Pendahuluan: Masa remaja adalah masa yang ditandai dengan adanya proses transisi dari masa kanak-kanak menuju masa dewasa. Pada usia remaja terjadi perubahan hormon, fisik, dan psikis yang berlangsung secara berangsur-angsur. Kemampuan mengendalikan emosi berbeda dengan meredam emosi. Rational emotive behaviour therapy (REBT) berfokus pada bagaimana orang berpikir, merasa dan bertindak untuk mengatasi emosional. Tujuan: Untuk mengidentifikasi pengaruh rational emotive behaviour therapy (REBT) terhadap kemampuan remaja dalam mengelola emosi. Metode: Pendekatan kuantitatif Quasi eksperimental pre-post with control group. Teknik pengambilan sampel menggunakan purposive sampling dengan total sampel sebanyak 80 partisipan yang terbagi menjadi 40 partisipan kelompok intervensi dan 40 kelompok kontrol. Analisis data menggunakan analisis univariat dan bivariat (uji dependent t-test). Hasil: Sebelum diberikan intervensi, mayoritas remaja dalam kelompok intervensi berada pada kategori sedang sebanyak 34 (85%), tinggi sebanyak 4 (10%), dan rendah sebanyak 2 (5%). Setelah intervensi, terjadi peningkatan yang signifikan yaitu dengan kategori tinggi kemampuan remaja mengelola emosi sebanyak 31 (77.5%) dan sedang sebanyak 9 (22.5%). Pada kelompok kontrol yang hanya mendapatkan bimbingan konseling dari guru BK, tidak terjadi peningkatan yang signifikan. Jumlah remaja dengan kemampuan tinggi menurun dari 7.5% menjadi 0%, sementara mayoritas tetap berada dalam kategori sedang. Hasil uji statistik perbedaan yang sangat signifikan antara kelompok intervensi dan kontrol (p=0.001), dengan rata-rata skor kemampuan mengelola emosi yang lebih tinggi secara bermakna pada kelompok yang mendapat intervensi REBT. Simpulan: Ada perbedaan mengelola emosi pada kelompok intervensi sebelum dan sesudah diberikan REBT dengan p-value = 0.001. Tidak ada perbedaan mengelola emosi pada kelompok kontrol sebelum dan sesudah mendapatkan bimbingan konseling dari guru BK dengan p-value = 0.766. Pemberian REBT dapat memberikan dampak yang signifikan dalam mengelola emosi pada remaja. Saran: Penerapan REBT secara kelompok dapat menjadi strategi intervensi yang efektif dalam membantu remaja mengelola emosi secara lebih sehat, rasional, dan adaptif. Kata Kunci: Emosi; Remaja; Rational Emotive Behaviour Therapy (REBT).